Collection management basics - Evans, G. Edward, 1937- (Library and information science text series, 2012)
"Now thoroughly revised for today's 21st-century library environment, this title provides a complete update of the classic Developing Library and Information Center Collections--the standard text and authority on collection development for all types of libraries and library school students since 1979"--